PERANAN TELEVISI BERBASIS DAKWAH ISLAM DALAM MENGUATKAN AKIDAH UMMAT - Triady, Bagus; Damayanti, Irma; Effendi, Erwan (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
The purpose of this study was to analyze the role of Islamic da'wah-based television in strengthening the faith of Muslims. The type of method used in this study is a qualitative method using secondary data. The results showed that in implementing the Islamic da'wah program through television media, there were several da'wah methods used, namely: the Talking Method, the insert method, and the Infiltration Method. In learning, television provides three important roles, namely the role in providing cognitive, affective and psychomotor benefits. Da'wah through television must contain a lot of information and ways of delivering it so that da'wah delivered through television can be received and interested by many people, namely by involving four main things, namely, renewal of the concept of da'wah, expansion and strengthening of networks or collaboration with institutions engaged in da'wah, strengthening primary and secondary funds to fund da'wah programs, and increasing the quality and quantity of da'i and da'iah, especially those that are already popular in television media.